Community Structure of Sea Cucumbers (Holothuroidea) in The Intertidal Zone of Koepisino Beach, North Buton - Aba, La; Pramesthi I. A, Dyah; Yanti, Yanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sea cucumbers are marine invertebrates belonging to the class Holothuroidea, living in various aquatic environments ranging from shallow coastal waters to deep seas. Sea cucumbers have an important ecological function in coral reef ecosystems. The aim of the research is to determine the community structure of sea cucumbers (Holothuroidea) in the intertidal zone of Koepisino Beach, North Buton. The research method used was quantitative descriptive research conducted in the intertidal zone of North Koepisino Buton Beach. Data collection was carried out by exploring each station measuring 50 × 100 meters for 3 stations. Data analysis was descriptive quantitative, In the intertidal zone of Koepisino Beach, North Buton, 12 species of sea cucumbers belonging to two orders, Aspidochirotida (genera Holothuria, Bohadschia, Telonata, and Stichopus) and Apodida (genera Synapta and Opheodesoma), were discovered. The community structure components analyzed in this study were abundance, diversity index, uniformity index, and dominance index.The highest abundance of sea cucumber species was at station I (sand substrate) at 0.009 (ind/m2). The lowest species abundance was at station III (coral rubble substrate) at 0.005 (ind/m2). H. scabra is the species with the highest abundance, namely 0.0026 ind/m2, while Bohadschia similis, Bohadschia vitiensis, Opheodesoma spectabilis, Telonata ananas are the species with the lowest abundance, namely 0 ind/m2. The Shannon-Wiener sea cucumber diversity index (H') is in the medium category 2.144. The sea cucumber uniformity index at the research location is high (E > 0.6) and there is no dominant species.